Exercise intolerance and fatigue in chronic heart failure: is there a role for group III/IV afferent feedback?. (1st November 2020) - Angius, Luca; Crisafulli, Antonio
Abstract: Exercise intolerance and early fatiguability are hallmark symptoms of chronic heart failure. While the malfunction of the heart is certainly the leading cause of chronic heart failure, the patho-physiological mechanisms of exercise intolerance in these patients are more complex, multifactorial and only partially understood. Some evidence points towards a potential role of an exaggerated afferent feedback from group III/IV muscle afferents in the genesis of these symptoms. Overactivity of feedback from these muscle afferents may cause exercise intolerance with a double action: by inducing cardiovascular dysregulation, by reducing motor output and by facilitating the development of central and peripheral fatigue during exercise. Importantly, physical inactivity appears to affect the progression of the syndrome negatively, while physical training can partially counteract this condition. In the present review, the role played by group III/IV afferent feedback in cardiovascular regulation during exercise and exercise-induced muscle fatigue of healthy people and their potential role in inducing exercise intolerance in chronic heart failure patients will be summarised.